Some Comments on Graduate Education in the Management Sciences - Lieberman, Gerald J. (Management Science, 1970)
The educational goal of a graduate program in the management sciences should be to adequately prepare a student for a lifetime pursuit of any phase of management science he chooses. More specifically, the program should be designed for a student who desires a management science education to meet his career goal in either a university, business or government position. However, any educational program must distinguish between the objectives of a doctoral student and a terminal master's student. A program leading to a Ph.D. degree should be directed to those primarily interested in a teaching and research career in University, or a research career in business or government Training at the master's level should emphasize applications of the techniques associated with management science. Such technically trained personnel are often used to develop advanced planning methods and/or operating policies within a company.